2010
DOI: 10.1097/iae.0b013e3181b32ebf
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Three-Gauge and 20-Gauge Vitrectomy in Epiretinal Membrane Surgery

Abstract: Twenty-three-gauge vitrectomy in epiretinal membrane surgery is comparable with 20-gauge vitrectomy and is a safe method with a low complication rate. However, the incidence of postoperative hypotony is more frequent using the 23-gauge system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
42
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 29 publications
12
42
1
3
Order By: Relevance
“…In this study, postoperative hypotony of 23-gauge TSV was 3.0%, which was comparable to 2.8% in Fine et al's Eye study 6 and that of 20-gauge vitrectomy was 0%, which was also similar to previous reports 13 . On the basis of statistically significant differences in the incidence of hypotony, our study confirmed the higher incidence of early postoperative hypotony in 23-gauge TSV, as previously reported.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In this study, postoperative hypotony of 23-gauge TSV was 3.0%, which was comparable to 2.8% in Fine et al's Eye study 6 and that of 20-gauge vitrectomy was 0%, which was also similar to previous reports 13 . On the basis of statistically significant differences in the incidence of hypotony, our study confirmed the higher incidence of early postoperative hypotony in 23-gauge TSV, as previously reported.…”
Section: Discussionsupporting
confidence: 79%
“…These studies were also limited in that only the intraocular pressure (IOP) at postoperative day 1 was studied and compared. 12,13 According to previous studies, the rate of wound leakage and hypotony in a small gauge sutureless system is supposed to be higher than that of 20-gauge conventional vitrectomy, but the difference has not been extensively evaluated through a direct comparison between the two gauges including various indications of vitrectomy and convincingly large number of patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, there are also reports of a much higher incidence, reaching up to 2.4%. 22 Such a frequency should, in general, give rise to careful procedural evaluations and is hardly attributable to the caliber of the ppv instrument, and reports of significant group differences 19,20 ought to be carefully scrutinized concerning methodical issues.…”
Section: Discussionmentioning
confidence: 99%
“…[68][69][70][71][72] In a comparative study, Haas et al showed that post-operative hypotony occurred significantly more often after 23G vitrectomy than after 20G vitrectomy. 73 76 Those authors assumed that open sclerotomies, combined with use of low-flow rate cutters, facilitated the invasion of bacteria to the vitreous cavity. Other factors that may play a role include postsurgery subconjunctival antibiotics, intraoperative use of corticosteroids and whether a partial or complete air-fluid exchange was performed at the end of surgery.…”
Section: Post-operative Complications Hypotonymentioning
confidence: 99%